Evaluation of Industrial Workplace Exposure to Metal Fumes using Toenail as Bio-Indicator - Zainal Bakri, Siti Farhana; Hariri, Azian; Ismail, Marzuki; Muhamad Damanhuri, Amir Abdullah (International Journal of Integrated Engineering, 2019)
The toxic gaseous generated from welding process contained a variety of heavy metals including the carcinogenic-type of metals. Widely, the occupational exposure to this toxic fume is associated with the occurrence of lung cancer and worker that exposed to this situation was considered as a high-risk group. This research was designed to determinate the amounts of heavy metals concentration in the breathing zone and toenail samples of exposed and non-exposed group. In this cross-sectional study, 36 individuals from automotive related industries, Malaysia were participated and classified as an exposed group (welder) and non-exposed group (control). The personal air sampling is collected in the breathing zone of the welder and for biomonitoring, toenail samples were collected from all 10 toes of each subject by using stainless-steel nail clippers and analysed by using inductively coupled plasma mass spectrometry (ICP-MS) according to ASTM D7439-08. The elements that were assessed in this research are Al, Cr, Mn, Fe, Co, Ni, Zn, Cu, As, Ag, and Pb. The heavy metals concentration found in the toenail of the exposed and non-exposed group is statistically difference except for Al, Mn, Fe, Co, Ni and Cu and the metal fume exposure that generated from different welding types in these three plant has shown a similar exposure to the welders.